Memperbaiki pola komunikasi pasangan melalui Behavioral Couple Therapy - Trisna Afdilla (Universitas Muhammadiyah Malang, 2022)
Communication is one of the keys to establish interaction and solve various problems for husband and wife. Patterns of communication and interaction in couples can affect various aspects of life in the household. Communication patterns in couples determine the quality of the relationship between husband and wife. When communication is ineffective, other problems arise such as the emergence of negative judgments on partners which results in dissatisfaction with the marriage. The purpose of this study is whether behavioral couple therapy is effective in improving the communication patterns of married couples. Data was collected by interview, observation and Dyadic Adjustment Scale. The intervention was carried out in 5 stages; lasted for 2 weeks until follow-up. The results of the intervention showed an increase in communication patterns in couples which was marked by an increase in behavioral changes and changes in partner interaction patterns.